Underwater Image Enhancement Using An Integrated Colour Model. - Iqbal, Kashif; Salam, Rosalina Abdul; Osman, Mohd. Azam; Talib, Abdullah Zawawi (International Association of Engineers., 2007)

(untitled)
In underwater situations, clarity of images are degraded by light absorption and scattering. This causes one colour to dominate the image. In order to improve the perception of underwater images, we proposed an approach based on slide stretching.